A neonatal morbidities and outcomes among late preterm infants - Sarvi, Jyoti B.; H., Sandeep V. (International Journal of Contemporary Pediatrics, 2020)
Background: Late preterm birth (34-36 weeks) infants are at greater risk of (2-3 fold) compared to near term or term babies. The present study was done with the purpose to examine related morbidities and outcomes among late preterm infants. Methods: The study included all late preterm babies (34 0/7 weeks-36 6/7 weeks) admitted to the Basaveshwar Teaching and General Hospital and Sangameshwar Hospital for a period of one and half year (December 2013-May 2015). Short term outcome was assessed in the form of neonatal morbidities and mortality during the study period. Results: A total of 203 late Preterm neonates comprised the study group. Male preponderance was noticed with a ratio of 1.5:1. This study confirmed that late-preterm infants are a population at risk of increased neonatal morbidity. Neonatal hyperbilirubinemia requiring phototherapy forms the major one followed by sepsis, respiratory distress, and feed intolerance. Majority of late preterm neonates required more than 7 days hospital duration. Conclusions: Late preterm infants suffer a large number of intercurrent medical problems during the neonatal period, especially increased likelihood of resuscitation in the delivery room, hypothermia, hypoglycemia, jaundice requiring phototherapy, respiratory pathologies, sepsis and feeding intolerance. Prolonging pregnancy to the maximum safest gestation will result in decrease in such morbidities.